2014
DOI: 10.1111/aogs.12499
|View full text |Cite
|
Sign up to set email alerts
|

Follow up of intima–media thickness after severe early‐onset preeclampsia

Abstract: IMT was not increased in women with an almost 5-year history of severe preeclampsia as an indicator of increased cardiovascular risk. This study suggests a transient adaptive response of the arteries in formerly preeclamptic women. The persistence of cardiovascular risk factors in this group emphasizes the need for long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
0
23
1
Order By: Relevance
“…We also demonstrated significant negative associations between preeclampsia onset and average cIMT in this study. No previous studies used preeclampsia onset as a continuous variable, but two studies found insignificant cIMT differences comparing women with previous very early preeclampsia onset (before 24 weeks of gestation) or women with previous severe early‐onset preeclampsia with women with previous normotensive pregnancies . Both studies had a smaller sample size and shorter follow up compared with the present study.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…We also demonstrated significant negative associations between preeclampsia onset and average cIMT in this study. No previous studies used preeclampsia onset as a continuous variable, but two studies found insignificant cIMT differences comparing women with previous very early preeclampsia onset (before 24 weeks of gestation) or women with previous severe early‐onset preeclampsia with women with previous normotensive pregnancies . Both studies had a smaller sample size and shorter follow up compared with the present study.…”
Section: Discussioncontrasting
confidence: 67%
“…Gestational age at delivery affects CVD risk after preeclampsia, as preeclamptic women with preterm deliveries have an even higher risk . However, only few studies have tested how gestational age at preeclampsia onset is associated with CVD risk later in life . At present, it is unclear whether gestational age at the clinical onset of preeclampsia can help identify previously preeclamptic women at highest CVD risk.…”
Section: Introductionmentioning
confidence: 99%
“…From the electronic database search, we identified 229 potentially eligible articles; a further five were identified through other sources (Figure ). Seventy‐six full‐text articles were reviewed and 22 were selected for inclusion in the systematic review (qualitative synthesis). Fourteen of the studies were included in the meta‐analysis (quantitative synthesis) and included studies that measured CIMT at the time of PE ( n = 7), and up to 10 years postpartum ( n = 10).…”
Section: Resultsmentioning
confidence: 99%
“…[43][44][45][46][47] Subclinical atherosclerosis is commonly assessed by carotid intima-media thickness (cIMT), coronary artery calcium score (CACS), coronary computed tomography angiography (CCTA) and cardiac magnetic resonance imaging (CMR). [5,[46][47][48][49][50][51][52][53][54][55][56][57][58] In recent years, some groups have started to evaluate these imaging techniques in former preeclampsia patients, as discussed below.…”
Section: Cardiovascular Imagingmentioning
confidence: 99%